Proposed parameters for improved ECC algorithm for NBI mitigation in DVBT system - Aizura binti Abdullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Orthogonal frequency division multiplexing (OFDM) is a popular multiplexing scheme and used by most communication standards such as Digital Video Broadcasting (DVB), Wireless Local Area Networks (WLANs) and Wireless Metropolitan Area Networks (WMANs). These systems are allowed to operate in unlicensed bands. Unlicensed wireless technologies are vulnerable to interference such as narrowband interference (NBI). Unwanted NBI signal with unaccepted power level will affect the quality of reception at the receiver and bit-error-rate (BER) performance of the system. Therefore, a sufficient mitigation technique is needed to mitigate NBI and error control coding (ECC) is proposed to solve the problem. The NBI problem considered for this research work is between OFDM-DVBT and IMT-A system. IMT-A system is an interferer to DVB-T system because according to World Radio Conference (WRC-07), the upper channel of DVB-T band (790MHz to 862MHz) is allocated for IMT-A (4G mobile applications). The method of exploiting error control code (ECC) in a system was known to assist the receiver in detecting and correcting the corrupted data due to noise. However, a specific ECC algorithm does not work for all type of noisy channel conditions and there is a possibility that the ECC does not work at all in recovering original data when the channel conditions are corrupted by NBI. Convolutional code (CC) is a suitable ECC to mitigate this problem as it is being used in broadcasting system as well as various communication standards such as DVB-T and WLANS. The development of 1/2 rate CC to mitigate NBI was considered by taking into account previous designs for modification. As a result, CC with small constraint length (K=3) and using different generator polynomials was proposed to mitigate the NBI effect. This work was simulated using MATLAB under additive white Gaussian noise (AWGN) channel using different types of modulation schemes which were 4-QAM and 16-QAM schemes. Simulation results showed that the proposed ECC scheme has a coding gain of 7dB for 4-QAM scheme and 8dB for 16-QAM scheme compared to a standard industrial design which gave faulty result. Bit error rate (BER) was used as performance measure to compare between transmitted and received bits.